SEROPREVALENCE OF TOXOPLASMA GONDII IN CANINES - A. Jadoon; T. Akhtar; A. Maqbool; A. A. Anjum; A. Ajmal (Journal of Animal and Plant Sciences, 2009)
A serological survey for Toxoplasmosis in dogs (n = 305) was conducted using a Latex agglutination test (LAT). The overall seroprevalence of Toxoplasma gondii in canines was 46.88 per cent. A total of 59 dogs were found seropositive by LAT at 1:256 titre giving an evidence of presence of infection. The seroprevalence of toxoplasmosis was inversely related to the age i.e. 52 % at 6 months and 32.5 % at 4 years and above. Non significant difference was observed in seropositivity between males (40%) and females (53.12) % and between exotic (46.15%) and local (57.14%) breeds. However significant variation in seropositivity was found between stray dogs (83.33%) and pet dogs (37.95 %) and between dogs having close contact with cats (55%) and with out cats (24.34%). Out of the tested bitches 60% were seropositive, mostly at 1:16 titre indicating residual immunity.
Keywords: Ananine; Latex agglutination test; seroprevalence; seropositive; toxoplasmosis; AIDS